Evaluasi Ketahanan Tanaman Kacang Tanah (Arachis Hypogaea) Terhadap Cekaman Kekeringan - Julvin Saputri Mendrofa; Dian Priskila Mendrofa; Berliana Vivi Lestari Lase; Kasih Iman Gulo; Ningsi Kristiani Mendrofa; Yoel Melsaro Larosa (CV. SINAR HOWUHOWU, 2025)
Drought is one of the major limiting factors in the cultivation of peanut (Arachis hypogaea L.), particularly in dryland and marginal areas. This study aims to evaluate the adaptive responses of peanut plants to drought stress through a comprehensive literature analysis. The approach combines a narrative review and meta-analysis of scientific studies published between 2010 and 2024. The analysis revealed that drought during the generative phase can reduce yield by up to 70–80%. Peanut plants exhibit various adaptive mechanisms, including root elongation, stomatal closure, increased activity of antioxidant enzymes (CAT and APX), accumulation of osmolytes (proline and agmatine), and enhanced levels of stress-related hormones such as abscisic acid (ABA). In addition, agronomic techniques such as seed priming with melatonin have been proven effective in enhancing drought tolerance by improving photosynthetic efficiency and cellular protection. This study highlights that the drought tolerance of peanut plants is a complex interaction between morphological, physiological, and molecular factors. Therefore, selecting drought-tolerant cultivars and applying adaptive cultivation technologies are key strategies for maintaining productivity under water-limited conditions.